2013
DOI: 10.1177/1056492613501227
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Basic Assumptions About Human Nature in Workplace Spirituality

Abstract: The very existence of workplace spirituality (WPS) is based on distinct assumptions about what it is to be human. However, to date, WPS has largely ignored ontological and epistemological roots that underpin how we theorize the person in management. This leaves WPS without a sound and distinct theoretical base. To address this important lacuna, we argue for a turn to existentialism, which, with its focus on the essence of the self, offers the opportunity to address this lacuna. We base our arguments on the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Although both of these streams have grown rapidly, they have grown largely in isolation from each other. The divide between these two streams of literature is obvious in the lack of conversations across them (Lips-Wiersma and Mills 2014). As a result, we have learned much about the diverse representations and consequences of spirituality, but we know little about the individual and organizational dynamics that might govern workplace spirituality.…”
Section: Introductionmentioning
confidence: 99%
“…Although both of these streams have grown rapidly, they have grown largely in isolation from each other. The divide between these two streams of literature is obvious in the lack of conversations across them (Lips-Wiersma and Mills 2014). As a result, we have learned much about the diverse representations and consequences of spirituality, but we know little about the individual and organizational dynamics that might govern workplace spirituality.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, spiritualism has gained considerable ground in behavioral science research. While many of those studies focused on the relationship between spiritualism and organizational performance, as well as employee's behavior in the workplace, however, positive relationships were obtained (Karakas & Sarigollu, 2019; Lips‐Wiersma & Mills, 2014). Fry (2013) concluded that spiritualism in the workplace has become a new value that opens a better way of studying organizational behavior.…”
Section: Literature Review and Model Developmentmentioning
confidence: 99%
“…Hence, in both countries, engaging in religion and spirituality research may be conceived as politically incorrect (in more than one sense). In the UK, positivist research in organizational spirituality and religion has fallen foul of the influential critical management movement (Lips-Wiersma & Mills, 2014) due to the apparent ‘commodification and appropriation of matters spiritual within predominantly capitalist forms of organization’ (Case & Gosling, 2010, p. 258; italics in original). Since from time immemorial academic scholarship is bound to dogma, conditioned by peer pressure and subject to institutional scrutiny, the conservatism, inherent to top tier journals (Altman & Laguecir, 2012) may have enacted a gate-keeping role to deny access to this field’s scholarship.…”
Section: Spirituality and Religionmentioning
confidence: 99%